2022
DOI: 10.3390/f13050663
|View full text |Cite
|
Sign up to set email alerts
|

Filtering Photon Cloud Data in Forested Areas Based on Elliptical Distance Parameters and Machine Learning Approach

Abstract: The Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2) was successfully launched. Due to its small spot size, multibeam configuration, high sampling rate, and strong immunity to terrain slopes, it has been regarded as a powerful tool for forest resources surveying and managing. However, the ICESat-2 photon cloud data contain considerable background photons, which discretely distribute in the background space of signal photons. Therefore, it is necessary to filter these noise photons. In this study, photons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For example, Meng et al [33] proposed a back propagation neural network denoising algorithm suitable for ICESat-2 photon data of shallow island and reef areas, and the results showed that the denoising algorithm has good denoising results in shallow island and reef areas. Li et al [34] used the support vector machine algorithm to classify signal photons and noise photons based on extracting elliptical distance parameters from ICESat-2 photon data in forest areas. The results showed that this method can effectively remove noise photons without relying on any statistical assumptions or thresholds, and the accuracy is higher than 0.98, which is superior to existing algorithms.…”
Section: Analysis Of Denoising Results In Different Beam Intensitiesmentioning
confidence: 99%
“…For example, Meng et al [33] proposed a back propagation neural network denoising algorithm suitable for ICESat-2 photon data of shallow island and reef areas, and the results showed that the denoising algorithm has good denoising results in shallow island and reef areas. Li et al [34] used the support vector machine algorithm to classify signal photons and noise photons based on extracting elliptical distance parameters from ICESat-2 photon data in forest areas. The results showed that this method can effectively remove noise photons without relying on any statistical assumptions or thresholds, and the accuracy is higher than 0.98, which is superior to existing algorithms.…”
Section: Analysis Of Denoising Results In Different Beam Intensitiesmentioning
confidence: 99%
“…ICESat-2 ATLAS photon-counting LiDAR emits weak signal pulses, its data contain a large number of background noise photons caused by solar background [42]. For the accuracy of the ensuing inversion of the forest parameters and mapping in this situation, the elimination of these noise photons is crucial [43]. For effectively controlling noise in photon-counting LiDAR data, a number of noise filtering algorithms have so far been established by earlier studies.…”
Section: B Atlas Data Processingmentioning
confidence: 99%
“…Li et al [ 28 ] and He et al [ 29 ] proposed a relative neighboring relationship (RNR) and local outlier factor algorithm with a rotating search area (LOFR) to improve the local parameter statistics algorithm. For supervised machine learning techniques, Li et al [ 30 ] and Chen et al [ 31 ] proposed the neighboring forward local density difference (NFLDD) and K-nearest neighbors distance to characterize the differences between the signals and noise. Supervised methods, such as random forest and support vector machine, were used to classify the photons, which achieved good accuracy, but these methods rely on a large number of training samples.…”
Section: Introductionmentioning
confidence: 99%
“…There are no unified tools and standards for preparing samples, making it difficult apply them widely. However, there is residual noise after single-level filtering algorithms [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], especially noise adjacent to the signal in complex terrains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation